Global Life Cycle Paper Flows, Recycling Metrics, and Material Efficiency. (6th June 2017) - Van Ewijk, Stijn; Stegemann, Julia A.; Ekins, Paul
Summary: Despite major improvements in recycling over the last decades, the pulp and paper sector is a significant contributor to global greenhouse gas emissions and other environmental pressures. Further reduction of virgin material requirements and environmental impacts requires a detailed understanding of the global material flows in paper production and consumption. This study constructs a Sankey diagram of global material flows in the paper life cycle, from primary inputs to end‐of‐life waste treatment, based on a review of publicly available data. It then analyzes potential improvements in material flows and discusses recycling and material efficiency metrics. The article argues that the use of the collection rate as a recycling metric does not directly stimulate avoidance of virgin inputs and associated impacts. An alternative metric compares paper for recycling (recovered paper) with total fibrous inputs and indicates that the current rate is at just over half of the technical potential. Material efficiency metrics are found to be more useful if they relate to the reuse potential of wastes. The material balance developed in this research provides a solid basis for further study of global sustainable production and consumption of paper. The conclusions on recycling and efficiency should be considered for improving environmental assessment and stimulating a shift toward resource efficiency and the circular economy.